PENGARUH TERPAAN KONTEN BROKEN STRINGS DI TIKTOK TERHADAP SIKAP GENERASI Z MENGENAI CHILD GROOMING - Berlian Rahmah Dewanto; Wahyu Budi Priatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of exposure to Broken Strings content on TikTok on Generation Z's attitudes toward child grooming. Broken Strings refers to a wave of content addressing the issue of child grooming that gained significant public attention in Indonesia between January and February 2026. The study employs an explanatory quantitative approach with purposive sampling, collecting data through an online questionnaire administered to 100 respondents aged 18–28 years, representing the Generation Z demographic. The findings indicate a positive and significant effect, with a t-value of 10.114 (sig. 0.000), a regression equation of Y = 18.509 + 0.651X, and an R-square value of 0.511. These results are interpreted through Albert Bandura's Social Learning Theory, which elucidates how exposure to TikTok content may shape audience attitudes through observational learning.